MODUS PENYELUNDUPAN NARKOTIKA DAN UPAYA PENANGGULANGANNYA DI LEMBAGA PEMASYARAKATAN KELAS II A DENPASAR - Suharyanti, Noni (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
The emergence of law’s fact about convicted criminal who involved in drugs crime case as a certain intention by the government, especially for law enforcer in order to sterilize the prison from the drugs. In Bali, the drugs smuggling into prison is even been occur in prison Class II A Denpasar, which found the kinds of drugs such as marijuana or methamphetamine in prison block. From the investigation of that case, in fact there is a certain modes which is used in order to the drugs can be enter to the prison. Therefore, it is important to study in depth about the drug smuggling and the mitigating effort in Prison Class II A Denpasar. The method which is used empirical law research with descriptive qualitative research. The data consists of primary data and secondary data. The technique of collecting data which is used the document study and interview technique. The technique of determine the sample used “non probability sampling”. The result found that mode that is used to smuggling the drug into prison in  vary such as : put inside the food, drink, threw the drugs from the outside, send a boy to delivered the food, etc. The effort that has been done by the Prison officer in Class II A Denpasar in mitigating the smuggling drug into prison by optimizes the preventive effort and repressive effort. Preventive effort was tighten the security and pacification in prison’s gate, sweeping in convict’s room, check every goods accurately which is entered into prison, and etc. However, the repressive effort was reported the smuggling or the convict who involved to the Police officer to get further law process.
Keywords: drug smuggling; mode; mitigating effort; prison